Effects of taxation on social innovation and implications for achieving Sustainable Development Goals in developing countries: A literature review - Jean C. Kouam; Simplice Asongu (African Governance and Development Institute (AGDI), 2022)
In developing countries, taxation is perceived as a brake on economic growth. Indeed, taxes in most of these countries are not sufficiently adapted to the specificity of the taxpayer and often do not consider the weak administrative capacity of the countries in the region. In this context, reforms have been initiated over the last decade to create tax environments that encourage savings, investment, entrepreneurship, and social innovation. This study provides an overview of research on the effects of taxation on social innovation and the corresponding implications for the achievement of Sustainable Development Goals (SDGs) in developing countries, taking three approaches: thematic, chronological, and methodological. Most studies agree that high taxes in business undermine social innovation and thus the achievement of SDGs, as social innovation is known to be a driver of most SDGs and business the vehicle. The majority of the selected studies used primary data collected from samples whose representativeness with respect to the population concerned (notably businesses) is still not explicitly justified.
Keywords: G20; I10; I20; I30; O10; 330; Social innovation; SDGs; developing countries